4=-(x-7)+3

Simple and best practice solution for 4=-(x-7)+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4=-(x-7)+3 equation:


Simplifying
4 = -1(x + -7) + 3

Reorder the terms:
4 = -1(-7 + x) + 3
4 = (-7 * -1 + x * -1) + 3
4 = (7 + -1x) + 3

Reorder the terms:
4 = 7 + 3 + -1x

Combine like terms: 7 + 3 = 10
4 = 10 + -1x

Solving
4 = 10 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
4 + x = 10 + -1x + x

Combine like terms: -1x + x = 0
4 + x = 10 + 0
4 + x = 10

Add '-4' to each side of the equation.
4 + -4 + x = 10 + -4

Combine like terms: 4 + -4 = 0
0 + x = 10 + -4
x = 10 + -4

Combine like terms: 10 + -4 = 6
x = 6

Simplifying
x = 6

See similar equations:

| 21dy+6xy-6xv-21dv= | | 8x+(-5)=35 | | Y=1.03x | | 2y+3y+30+4x-100+x+5=360 | | f(1)=1(1)+3 | | vw+uw=uv | | 2x+(x+6)=54 | | -2a-6a=24 | | (w^2-4w+7)+(3w^2+5w-3)= | | 2y-36x=45-38y | | 1350=45x+30y | | 10=8-4y | | 3x*ln(x+3)+4=0 | | 11w+2(3w-1)=5 | | (9y-6)(1.5)+3.5y= | | 3.50x+40=57.50 | | 7n+n=64 | | 30x^2-25x=0 | | 2(2x+3)=24 | | -2c-24=2c-12 | | 9u-5u=36 | | 5x+2=-5 | | 6-3x=14x+2 | | 13=7r-6-2 | | 8p-6(1-2p)=86 | | x+(x+2)=116 | | n+4.1n+6=-1.5(n+4.8) | | -3(4x-8)=2-4(3x-7) | | -16x^2+64x-26=0 | | 3x-8=-24 | | 8p-6(1-2b)=86 | | a+220=x-2(x+5)2 |

Equations solver categories